2010
DOI: 10.1124/jpet.109.164970
|View full text |Cite
|
Sign up to set email alerts
|

Metformin, an Antidiabetic Agent, Suppresses the Production of Tumor Necrosis Factor and Tissue Factor by Inhibiting Early Growth Response Factor-1 Expression in Human Monocytes in Vitro

Abstract: Metformin, an antidiabetic agent, has been shown to reduce atherothrombotic disease in diabetic patients independent of antihyperglycemic effect. Recent studies have demonstrated that metformin attenuates the proinflammatory responses in human vascular wall cells and macrophages. However, the detailed molecular mechanisms underlying these therapeutic effects remain unclear. In the present study, we investigated the effects of metformin on tumor necrosis factor (TNF) production and tissue factor (TF) expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 32 publications
(51 reference statements)
4
70
0
4
Order By: Relevance
“…In our model using primary human MDMs, AMPK activation by ETC-1002 inhibits LPSinduced MAPK signaling as refl ected in the reduced phosphorylation of JNK and p38. Similar inhibition of JNK and p38 phosphorylation has been previously demonstrated for AMPK activators in macrophage cell lines as well as in human monocytes where pharmacological activation of AMPK offsets immune responses in a MAPK-dependent fashion ( 26,30 ).…”
Section: Etc-1002 Reduces Epididymal Fat-pad Mass and Adipose Tissue mentioning
confidence: 56%
See 1 more Smart Citation
“…In our model using primary human MDMs, AMPK activation by ETC-1002 inhibits LPSinduced MAPK signaling as refl ected in the reduced phosphorylation of JNK and p38. Similar inhibition of JNK and p38 phosphorylation has been previously demonstrated for AMPK activators in macrophage cell lines as well as in human monocytes where pharmacological activation of AMPK offsets immune responses in a MAPK-dependent fashion ( 26,30 ).…”
Section: Etc-1002 Reduces Epididymal Fat-pad Mass and Adipose Tissue mentioning
confidence: 56%
“…In clinical studies, ETC-1002 has not only demonstrated improved lipid profi les but also revealed signifi cantly attenuated levels of hsCRP ( 19 ), an independent risk factor for CAD and a well-established clinical biomarker of infl ammation ( 20,21 ). Pharmacological activation of AMPK has been previously shown to limit infl ammatory response in vitro and in vivo (22)(23)(24)(25)(26), and several signaling pathways, including Akt, GSK, SIRT, and NFkB, have been associated with anti-infl ammatory consequences of AMPK activation ( 17,(27)(28)(29). While the exact mechanism of AMPK-dependent regulation of the immune response remains unclear, inhibition of mitogen-activated protein kinases (MAPK), such as JNK and p38, has been recently linked to AMPK-dependent anti-infl ammatory signaling ( 30 ).…”
Section: Protein Arraysmentioning
confidence: 99%
“…estrogen, in cigarette smokers and in hyperhomocysteinemia [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] .…”
Section: Inflammationmentioning
confidence: 99%
“…Like tumor necrosis factor-alpha (TNF-α), nuclear factor-kappa B (NF-kB) and signal transducer and activator of transcription 3 (STAT3) are important components of the inflammation reaction. Arai et al elucidated that metformin reduces the process and production of TNF-α in human monocytes [17].…”
Section: Inflammatory Pathway and Metforminmentioning
confidence: 99%